Understanding romance fraud: insights from domestic violence research - Cross, Cassandra (The British journal of criminology, 2018)
Romance fraud affects thousands of victims globally, yet few scholars have studied it. The dynamics of relationships between victims and offenders are not well understood, and the effects are rarely discussed. This article adapts the concept of psychological abuse from studies of domestic violence to better understand romance fraud. Using interviews with 21 Australian romance fraud victims, we show how offenders use non-violent tactics to ensure compliance with ongoing demands for money. This article identifies similarities and differences between domestic violence and romance fraud. We argue that thinking through domestic violence and romance fraud together offers potential benefits to both bodies of research.